Evaluating U.S. purity culture’s impact on female sexual health and development - Pugh, Mary-Joy (My University, 2025)
The purpose of this research was to investigate the impact of Christian purity culture on the sexual health and development of emerging adult women in the United States. Using self-determination theory and social script theory, the research explores how exposure to purity culture and the internalization of Christian messages via identification and introjection impact sexual health outcomes, including functioning, guilt, pleasure, and first coital affect. The study also examines mediating and moderating variables including age and relationship status at the time of first intercourse. Using a mixed sample (N = 300) of college-attending and national panel participants, women aged 18-29 were asked to complete a retrospective online Qualtrics survey assessing exposure to purity culture, sexual health indicators, and religious internalization. Path analyses were conducted to test three hypotheses referencing the relationships among purity culture, religious internalization, and sexual health outcomes. Results indicated that exposure to purity culture beliefs in childhood is associated with poorer sexual health outcomes in emerging adult women, particularly when religious values are internalized through introjection rather than identification. Identification, while also associated with guilt, was positively associated with sexual pleasure, functioning, and older age at first intercourse, suggesting a buffering effect against the negative impacts of purity culture. Guilt was identified as a mediating factor in sexual health outcomes, and relationship status was found to moderate associations between purity culture and introjection, purity culture and guilt, and introjection and guilt. Findings contribute to a deeper understanding of how religious socialization and sexual scripts influence female sexual development and may inform future sexual education and mental health interventions. Ultimately, purity culture has a net negative influence on women’s sexual health outcomes, although the way its messages are internalized can mitigate the impact.
Keywords: Purity culture; Women's health; Emerging adulthood; Sexual health; Religious internalization